(untitled) (Research, Society and Development, 2020)
Two new rapid descriptive sensory evaluation methods have been gaining ground in the field sensory evaluation. The Projective Mapping method uses similarities and dissimilarities as a criterion, while Pivot Profile, uses reference criteria. This research aimed to assess panels with 12 and 24 judges, comparing its reproducibility, and evaluate if a non trained panel with a smaller numbers of judges is sufficient for results reliability. Samples of Pilsen beers in different packages were distributed, as well as a reference sample, with different sensorial characteristics. It was possible to observe a slight discrepancy between the results obtained in each of the applied tests. We observed a need for short-term training before the application of the test, aiming for better use of the descriptive terms by the judges. Also, the number of judges influenced the obtained results, being the panels of 24, in both tests, the ones that best described the indicated characteristics.